Equilibrium phase structures for BiFeO3 thin films on LaAlO3 substrate - Huang, C. W. (2013)
The stable phase structure of BiFeO3 films on LaAlO3 substrate was studied. In the biaxial constrained case, it changes from a tetragonal phase to a rhombohedral one with the increase of film thickness. By reducing the degree of the constrain from the biaxial case to the uniaxial one, the film relaxes in a much smaller thickness to a rhombohedral phase and an enhanced piezoelectric response is predicted in comparison to that of biaxial constrained case.